Perspectives of South Korean School Principals on Job Satisfaction: In Comparison to German and U.S. Principals. Issue 4 (2nd October 2021) - Wang, Chuang; Hancock, Dawson R.; Lim, Jae Hoon; Müller, Ulrich; Tulowitzki, Pierre; Stricker, Tobias
ABSTRACT: To meet the challenge of recruiting and retaining principals, this study examined school principal's perspectives of factors that might influence their decisions to remain in their positions as well as barriers that would have discouraged them to become principals. The sample consisted of 119 school principals in South Korea, 117 school principals in Germany and 123 school principals in the United States. Differences between their current and expected job satisfactions uncovered important findings regarding salary, recognition, principal authority, resources, balance between work and life, and school safety. Implications for school district policy and school leadership are discussed.